UPAYA MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE COURSE REIVEW HORAY PADA MATA PELAJARAN IPA DI KELAS IV SD SWASTA ST. PETRUS MEDAN TAHUN PEMBELAJARAN 2018/2019 - TARIGAN, EKA SRINAITA YAPULINA (Jurnal Ilmiah Aquinas, 2019)
The research used is Classroom Action Research (CAR) which aims to determine the improvement of student learning outcomes by using the Course Reivew Horay type of cooperative learning model in science subjects with the material of efforts to balance and preserve natural resources in their environment in private IV-A elementary school St. Petrus Medan Learning Year 2018/2019. Subjects in this study were students of grade IV-A Elementary School Private St. Petrus Medan Learning Year 2018/2019 totaling 28 students, consisting of 14 female students and 14 male students. The object in this study is Classroom Action Research (CAR) by applying two cycles, namely cycle I and cycle II which includes planning, implementation, observation, and reflection. The results of this study indicate an increase in student learning outcomes in science subjects with the material of efforts to balance and preserve natural resources in their environment in class IV-A Elementary School of Private St. Petrus Medan Learning Year 2017/2018. This is evident from the results of the research that has been done on the students' pre-test scores that are complete only 1 student or 3.57% while the students who are not complete are 27 students or 96.43%, then continued the research in the first cycle of students who got complete scores only 15 students or 53.58% of students who did not complete as many as 13 students or 46.42% then experienced an increase in the first cycle compared to the pretest. In the implementation of the first cycle, it still does not meet the predetermined completeness category. Then continued the research in the second cycle, namely students who got complete scores as many as 25 students or 89.29% while students who did not complete only 3 students or 10.71% then experienced an increase in the second cycle compared to the first cycle and have fulfilled the predetermined completeness . Furthermore, the teacher's activities on observation cycle I gained an average of 62% and in the second cycle increased to 84%. While the activities of students in the learning process obtain an average of 70 and in cycle II has increased to 80. ` Thus it can be concluded by using the Course Reivew Horay type of cooperative learning model on natural science subjects in the effort to balance and preserve natural resources in their environment in class IV-A SD St. Petrus Medan can improve student learning outcomes. So it is recommended for further learning to use it.